2017
DOI: 10.17219/dmp/80101
|View full text |Cite
|
Sign up to set email alerts
|

Hand eczema among Lebanese dentists: An epidemiological study

Abstract: Background. Dentists are at risk of developing hand eczema, as are most people who work in the health care field.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…There were also statistical differences between different dentistry specialties, for example, neck pain was highest among endodontic dentists while back pain was highest among pediatric dentists. Also, female dentists reported suffering more than male dentists concerning neck and wrist levels [ 33 ].…”
Section: Reviewmentioning
confidence: 99%
“…There were also statistical differences between different dentistry specialties, for example, neck pain was highest among endodontic dentists while back pain was highest among pediatric dentists. Also, female dentists reported suffering more than male dentists concerning neck and wrist levels [ 33 ].…”
Section: Reviewmentioning
confidence: 99%
“…Similarly, MSDs among dental practitioners in Jeddah and Riyadh were 70% and 90.2%, respectively [11,12]. Moreover, many authors reported an increased association between the dental profession and hand/wrist pain [8,[15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…These findings suggest that dental professionals primarily use upper body regions at work [18]. Especially during the treatment of patients and administrative work, which account for around 70% of all dental tasks, upper extremities like the hand/wrist or shoulder are increasingly under muscular strain Thus, dental professionals are particularly vulnerable to musculoskeletal diseases and pain in the shoulder and hand/wrist too [19].…”
Section: Discussionmentioning
confidence: 99%